ANTHROPOMETRIC AND THORACIC CHANGES IN MIDDLE-AGED AND ELDERLY WOMEN 12, 24, AND 36 MONTHS AFTER MASTECTOMY WITH THE USE OF THERAPEUTIC EXERCISE - Xodjayeva Dilrux Ilxomovna (Modern American Journals, 2025)
This study analyzes the dynamics of anthropometric and thoracic parameters in middle-aged and elderly women during rehabilitation following mastectomy over a 36-month period, with a focus on the effects of therapeutic physical exercise (TPE). A total of 120 women were included, divided into two age groups: middle-aged (45–59 years) and elderly (60–74 years). Measurements were conducted at 12, 24, and 36 months post-surgery. Anthropometric parameters such as height, body weight, BMI, torso length, and sitting height were assessed. In addition, chest circumference at rest, during inhalation and exhalation, and chest excursion were evaluated. Statistically significant improvements were observed in both groups, especially among middle-aged women, with a consistent decrease in body mass and BMI, along with more stable values in chest expansion and circumference over time.